The Digital Knowledge Economy Index: Mapping Content Production. Issue 12 (2nd December 2019) - Ojanperä, Sanna; Graham, Mark; Zook, Matthew
ABSTRACT: We propose the construction of a Digital Knowledge Economy Index, quantified by way of measuring content creation and participation through digital platforms, namely the code sharing platform GitHub, the crowdsourced encyclopaedia Wikipedia, and Internet domain registrations and estimating a fifth sub-index for the World Bank Knowledge Economy Index for year 2012. This approach complements conventional data sources such as national statistics and expert surveys and helps reflect the underlying digital content creation, capacities, and skills of the population. An index that combines traditional and novel data sources can provide a more revealing view of the status of the world's digital knowledge economy and highlight where the (un)availability of digital resources may actually reinforce inequalities in the age of data.